Cardioprotective effect of curcumin on myocardial ischemia/reperfusion injury: a meta-analysis of preclinical animal studies - Zeng, Yi-Fan; Guo, Qi-Hao; Wei, Xin-Yu; Chen, Si-Yu; Deng, Sheng; Liu, Ji-Jia; Yin, Ni; Liu, Yan; Zeng, Wen-Jing (Frontiers in Pharmacology, 2023)
Objective: This meta-analysis aimed to determine the efficacy of curcumin in preventing myocardial ischemia/reperfusion(I/R) injury in animal models. Methods: Studies published from the inception to January 2023 were systematically searched in databases including PubMed, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), Wan-Fang database, and VIP database (VIP). The SYRCLE’s RoB tool was used to determine methodological quality. Sensitivity analysis and subgroup analysis were performed when there was high heterogeneity. Publication bias was assessed using a funnel plot. Results: Thirty-eight studies involving 771 animals were included in this meta-analysis with methodology quality scores ranging from 4 to 7. The results indicated that curcumin treatment significantly improved myocardial infarction size (SMD=-5.67; 95% CI: -6.91, -4.43; P<0.01; I2=84%). Sensitivity analysis for infarct size showed that the results were stable and reliable. However, the funnel plot was asymmetric. Subgroup analysis included species, animal model, dose, administration, and duration. The results showed that the subgroup dose was statistically significant between subgroups. In addition, curcumin treatment improved cardiac function, myocardial injury enzymes, and oxidative stress levels in animal models of myocardial I/R injury. The funnel plot revealed that there is publication bias for creatine kinase and lactate dehydrogenase. Finally, we performed a meta-analysis of inflammatory cytokine and apoptosis index. The results showed that curcumin treatment down-regulated serum inflammatory cytokine levels and myocardial apoptosis index. Conclusion: This meta-analysis suggests that curcumin has excellent potential for the treatment of myocardial I/R injury in animal models. However, this conclusion needs to be further discussed and verified in large animal models and clinical trials.